A rapid and convenient method for synthesis of anilinoquinazoline: an improved synthesis of erlotinib derivatives - Zahra Haghighijoo; Zahra Rezaei; SamanehTaheri; Meisam Jani; Soghra Khabnadideh (Shiraz University of Medical Sciences, 2015)
4-Anilinoquinazolines have been widely studied as anticancer agents. Despite the widespread use of this class of compounds, the reported syntheses of 4-anilinoquinazolines require multistep and lowyielding reaction pathways. In this study, a novel strategy to prepare 4-anilinoquinazoline derivatives based on the cyclization of anthranilic acid is described. By using dichloroanthranilic acid, the quinazoline ring was etherified in order to mimic the erlotinib structure as a tyrosine kinase inhibitor. The new compounds contain different substitutions at the meta-positions of the quinazoline ring instead of the ortho-positions of erlotinib. Ten new 4-anilinoquinazoline derivatives were sysnthesized (21-30) in only 4 steps with desirable yields.